Recent advances in fuzzy sets, intuitionistic fuzzy sets, generalized nets and related topics. Volume I: foundations * The intuitionistic fuzzy sets as constructive objects - Atanassov, Krassimir Todorov (1954– ) (Instytut Badań Systemowych. Polska Akademia Nauk, 2011)
It is shown that the intuitionistic fuzzy sets and in particular – the fuzzy sets, can be interpreted as constructive objects. A criterion for constructiveness is introduced. It is proved that all operations and operator over intuitionistic fuzzy sets are also constructive objects.
[1-4], 1-23 stron ; 21 cm
Bibliografia s. 22-23